THE IMPORTANCE OF STUDYING THE DIALECTAL LEXICON OF THE ENGLISH LANGUAGE (Scientific journal of the Fergana State University, 2026)
The English language, despite its global status, remains internally diverse, especially at the lexical level of local dialects. This article examines the significance of studying English dialectal vocabulary from lexicological, sociolinguistic, and cultural perspectives. Dialect words often preserve archaic roots and meanings. Their usage reflects the speaker’s social identity and regional culture. Studying dialectal lexicon deepens knowledge of the language’s history and evolution, reveals societal attitudes toward linguistic variation, and contributes to preserving the linguistic and cultural heritage of English.